To go, or not to go? Modelling the effects of employment decentralisation on telecommuting preferences - Muhammad Sofian Mohamed Tahir (Nanyang Technological University, 2021)
Employment decentralisation and telecommutinghavebothbeen proposed asdemand-orientedsolutions to managepeak-hour congestion intothe Central Business District (CBD).However, in dynamic urban systems, theirinteractivity mayinfluence how muchthey may reduce peak hour travel demand. This project aims to provide perspectives on how employment decentralisation may influence telecommuting preferencesin ordertorefine existing integrated land use and transport planningstrategies.Astructural equation model was developedfrom a scenario-based stated preference survey depicting various workplace locations, crowdedness levels and commutetimesamong employeesin Singaporewho commute usingthe Mass Rapid Transit (MRT) system. Focus interviews wereconductedto understand transport planning processesinaddressingthe variabilityin ridership.It was found that only current employment location can besignificantly associated with travel benefits. Similarly, travel benefits only positively affectedinduced demand from reduced crowdedness. Reduced preferencesto telecommutewere more significantly influenced by reduced crowdedness vis-à-vis shortened commute times. Interviewsfurtheremphasisedthe need for complementary transport networks and a demand-responsive approach to cater to ridership fluctuations.In essence, this project contributes to existing literature by reaffirmingthe need for an integrated approach in urban and transport planning to manoeuvre through future uncertainties.